One-Step Fabrication of Hierarchically Structured Silicon Surfaces and Modification of Their Morphologies Using Sacrificial Layers. (8th July 2013) - Cho, Seong J.; Seok, Se Yeong; Kim, Jin Young; Lim, Geunbae; Lim, Hoon
Abstract : Fabrication of one-dimensional nanostructures is a key issue for optical devices, fluidic devices, and solar cells because of their unique functionalities such as antireflection and superhydrophobicity. Here, we report a novel one-step process to fabricate patternable hierarchical structures consisting of microstructures and one-dimensional nanostructures using a sacrificial layer. The layer plays a role as not only a micromask for producing microstructures but also as a nanomask for nanostructures according to the etching time. Using this method, we fabricated patterned hierarchical structures, with the ability to control the shape and density of the nanostructure. The various architectures provided unique functionalities. For example, our sacrificial-layer etching method allowed nanostructures denser than what would be attainable with conventional processes to form. The dense nanostructure resulted in a very low reflectance of the silicon surface (less than 1%). The nanostructured surface and hierarchically structured surface also exhibited excellent antiwetting properties, with a high contact angle (>165°) and low sliding angle (<1°). We believe that our fabrication approach will provide new insight into functional surfaces, such as those used for antiwetting and antireflection surface applications.